Understanding and treating pathological narcissism - Ogrodniczuk, John S. (American Psychological Association, 2013)
"Understanding and Treating Pathological Narcissism is intended to provide an overview of important issues related to the psychotherapeutic treatment of patients with this debilitating condition. The book draws on the knowledge of highly skilled, well-respected contributors who are at the forefront of clinical and empirical advances in the field, and the concise chapters provide an introduction to various topics that are relevant to the treatment of patients with pathological narcissism. This point deserves emphasis: This book should not be perceived as a comprehensive treatment guide or definitive textbook on pathological narcissism, but rather as a synopsis of key issues that provides the reader with a basic grounding. The complexity of pathological narcissism cannot be addressed comprehensively in the space of a series of short chapters. That being said, the unique focus and the breadth of topics covered herein should make this book a useful clinical reference"--Introduction. (PsycINFO Database Record (c) 2012 APA, all rights reserved).